Cross-dehydrogenative coupling for the intermolecular C–O bond formation - Krylov, Igor B.; Vil’, Vera A.; Terent’ev, Alexander O. (Beilstein Journal of Organic Chemistry, 2015)
The present review summarizes primary publications on the cross-dehydrogenative C–O coupling, with special emphasis on the studies published after 2000. The starting compound, which donates a carbon atom for the formation of a new C–O bond, is called the CH-reagent or the C-reagent, and the compound, an oxygen atom of which is involved in the new bond, is called the OH-reagent or the O-reagent. Alcohols and carboxylic acids are most commonly used as O-reagents; hydroxylamine derivatives, hydroperoxides, and sulfonic acids are employed less often. The cross-dehydrogenative C–O coupling reactions are carried out using different C-reagents, such as compounds containing directing functional groups (amide, heteroaromatic, oxime, and so on) and compounds with activated C–H bonds (aldehydes, alcohols, ketones, ethers, amines, amides, compounds containing the benzyl, allyl, or propargyl moiety). An analysis of the published data showed that the principles at the basis of a particular cross-dehydrogenative C–O coupling reaction are dictated mainly by the nature of the C-reagent. Hence, in the present review the data are classified according to the structures of C-reagents, and, in the second place, according to the type of oxidative systems. Besides the typical cross-dehydrogenative coupling reactions of CH- and OH-reagents, closely related C–H activation processes involving intermolecular C–O bond formation are discussed: acyloxylation reactions with ArI(O2CR)2 reagents and generation of O-reagents in situ from C-reagents (methylarenes, aldehydes, etc.).
Keywords: acyloxylation; alkoxylation; C–H functionalization; C–O bond formation; cross-dehydrogenative coupling; oxidative cross-coupling

(untitled) - Li, C.-J.; Li, Z. (Pure Appl. Chem., 2006)

(untitled) - Li, Z.; Bohle, D. S.; Li, C.-J. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Beccalli, E. M.; Broggini, G.; Martinelli, M.; Sottocornola, S. (Chem. Rev., 2007)

(untitled) - Li, C.-J. (Acc. Chem. Res., 2009)

(untitled) - Scheuermann, C. J. (Chem. – Asian J., 2010)

(untitled) - Yoo, W.-J.; Li, C.-J. (Top. Curr. Chem., 2010)

(untitled) - Yeung, C. S.; Dong, V. M. (Chem. Rev., 2011)

(untitled) - Cho, S. H.; Kim, J. Y.; Kwak, J.; Chang, S. (Chem. Soc. Rev., 2011)

(untitled) - Sun, C.-L.; Li, B.-J.; Shi, Z.-J. (Chem. Rev., 2011)

(untitled) - Zhang, C.; Tang, C.; Jiao, N. (Chem. Soc. Rev., 2012)

(untitled) - Song, G.; Wang, F.; Li, X. (Chem. Soc. Rev., 2012)

(untitled) - Hirano, K.; Miura, M. (Chem. Commun., 2012)

(untitled) - Liu, C.; Liu, D.; Lei, A. (Acc. Chem. Res., 2014)

(untitled) - Girard, S. A.; Knauber, T.; Li, C.-J. (Angew. Chem., Int. Ed., 2014)

(untitled) - Samanta, R.; Matcha, K.; Antonchick, A. P. (Eur. J. Org. Chem., 2013)

(untitled) - Hoffman, R. V.; Wilson, A. L.; Kim, H. O. (J. Org. Chem., 1990)

(untitled) - Lifchits, O.; Demoulin, N.; List, B. (Angew. Chem., Int. Ed., 2011)

(untitled) - Jones, K. M.; Tomkinson, N. C. O. (J. Org. Chem., 2012)

(untitled) - Liu, B.; Shi, B.-F. (Tetrahedron Lett., 2015)

(untitled) - Liu, G.; Wu, Y. (Top. Curr. Chem., 2010)

(untitled) - Liron, F.; Oble, J.; Lorion, M. M.; Poli, G. (Eur. J. Org. Chem., 2014)

(untitled) - Wu, X.-F.; Gong, J.-L.; Qi, X. (Org. Biomol. Chem., 2014)

(untitled) - Ananikov, V. P.; Khemchyan, L. L.; Ivanova, Yu. V.; Bukhtiyarov, V. I.; Sorokin, A. M.; Prosvirin, I. P.; Vatsadze, S. Z.; Medved'ko, A. V.; Nuriev, V. N.; Dilman, A. D.; Levin, V. V.; Koptyug, I. V.; et al. (Russ. Chem. Rev., 2014)

(untitled) - Ekoue-Kovi, K.; Wolf, C. (Chem. – Eur. J., 2008)

(untitled) - Stowers, K. J.; Sanford, M. S. (Org. Lett., 2009)

(untitled) - Anand, M.; Sunoj, R. B. (Org. Lett., 2011)

(untitled) - Zhu, W.; Wang, H.; Peng, H.; Liu, G.; Guo, Y. (Chin. J. Chem., 2013)

(untitled) - Desai, L. V.; Stowers, K. J.; Sanford, M. S. (J. Am. Chem. Soc., 2008)

(untitled) - Racowski, J. M.; Dick, A. R.; Sanford, M. S. (J. Am. Chem. Soc., 2009)

(untitled) - Powers, D. C.; Ritter, T. (Acc. Chem. Res., 2012)

(untitled) - Camasso, N. M.; Pérez-Temprano, M. H.; Sanford, M. S. (J. Am. Chem. Soc., 2014)

(untitled) - Dick, A. R.; Kampf, J. W.; Sanford, M. S. (J. Am. Chem. Soc., 2005)

(untitled) - Dick, A. R.; Hull, K. L.; Sanford, M. S. (J. Am. Chem. Soc., 2004)

(untitled) - Kalyani, D.; Sanford, M. S. (Org. Lett., 2005)

(untitled) - Ye, Z.; Wang, W.; Luo, F.; Zhang, S.; Cheng, J. (Org. Lett., 2009)

(untitled) - Hu, C.-J.; Zhang, X.-H.; Ding, Q.-P.; Lv, T.; Ge, S.-P.; Zhong, P. (Tetrahedron Lett., 2012)

(untitled) - Li, L.; Yu, P.; Cheng, J.; Chen, F.; Pan, C. (Chem. Lett., 2012)

(untitled) - Bian, Y.-J.; Xiang, C.-B.; Chen, Z.-M.; Huang, Z.-Z. (Synlett, 2011)

(untitled) - Rout, S. K.; Guin, S.; Gogoi, A.; Majji, G.; Patel, B. K. (Org. Lett., 2014)

(untitled) - Chen, X.; Hao, X.-S.; Goodhue, C. E.; Yu, J.-Q. (J. Am. Chem. Soc., 2006)

(untitled) - Dudkina, Y. B.; Mikhaylov, D. Y.; Gryaznova, T. V.; Tufatullin, A. I.; Kataeva, O. N.; Vicic, D. A.; Budnikova, Y. H. (Organometallics, 2013)

(untitled) - Zheng, X.; Song, B.; Xu, B. (Eur. J. Org. Chem., 2010)

(untitled) - Leng, Y.; Yang, F.; Zhu, W.; Wu, Y.; Li, X. (Org. Biomol. Chem., 2011)

(untitled) - Kamal, A.; Srinivasulu, V.; Sathish, M.; Tangella, Y.; Nayak, V. L.; Rao, M. P. N.; Shankaraiah, N.; Nagesh, N. (Asian J. Org. Chem., 2014)

(untitled) - Wang, Z.; Kuang, C. (Adv. Synth. Catal., 2014)

(untitled) - Shi, S.; Kuang, C. (J. Org. Chem., 2014)

(untitled) - Bhadra, S.; Matheis, C.; Katayev, D.; Gooßen, L. J. (Angew. Chem., Int. Ed., 2013)

(untitled) - Li, W.; Sun, P. (J. Org. Chem., 2012)

(untitled) - Wang, G.-W.; Yuan, T.-T. (J. Org. Chem., 2010)

(untitled) - Jiang, T.-S.; Wang, G.-W. (J. Org. Chem., 2012)

(untitled) - Wang, G.-W.; Yuan, T.-T.; Wu, X.-L. (J. Org. Chem., 2008)

(untitled) - Yadav, M. R.; Rit, R. K.; Sahoo, A. K. (Chem. – Eur. J., 2012)

(untitled) - Rit, R. K.; Yadav, M. R.; Sahoo, A. K. (Org. Lett., 2014)

(untitled) - Desai, L. V.; Malik, H. A.; Sanford, M. S. (Org. Lett., 2006)

(untitled) - Wang, L.; Xia, X.-D.; Guo, W.; Chen, J.-R.; Xiao, W.-J. (Org. Biomol. Chem., 2011)

(untitled) - Neufeldt, S. R.; Sanford, M. S. (Org. Lett., 2010)

(untitled) - Padala, K.; Jeganmohan, M. (Chem. Commun., 2013)

(untitled) - Reddy, B. V. S.; Revathi, G.; Reddy, A. S.; Yadav, J. S. (Tetrahedron Lett., 2011)

(untitled) - Péron, F.; Fossey, C.; Sopkova-de Oliveira Santos, J.; Cailly, T.; Fabis, F. (Chem. – Eur. J., 2014)

(untitled) - Yin, Z.; Jiang, X.; Sun, P. (J. Org. Chem., 2013)

(untitled) - Zhang, C.; Sun, P. (J. Org. Chem., 2014)

(untitled) - Zhang, S.-Y.; He, G.; Zhao, Y.; Wright, K.; Nack, W. A.; Chen, G. (J. Am. Chem. Soc., 2012)

(untitled) - Chen, F.-J.; Zhao, S.; Hu, F.; Chen, K.; Zhang, Q.; Zhang, S.-Q.; Shi, B.-F. (Chem. Sci., 2013)

(untitled) - Gou, F.-R.; Wang, X.-C.; Huo, P.-F.; Bi, H.-P.; Guan, Z.-H.; Liang, Y.-M. (Org. Lett., 2009)

(untitled) - Chan, L. Y.; Meng, X.; Kim, S. (J. Org. Chem., 2013)

(untitled) - Roane, J.; Daugulis, O. (Org. Lett., 2013)

(untitled) - Hao, X.-Q.; Chen, L.-J.; Ren, B.; Li, L.-Y.; Yang, X.-Y.; Gong, J.-F.; Niu, J.-L.; Song, M.-P. (Org. Lett., 2014)

(untitled) - Zhang, L.-B.; Hao, X.-Q.; Zhang, S.-K.; Liu, K.; Ren, B.; Gong, J.-F.; Niu, J.-L.; Song, M.-P. (J. Org. Chem., 2014)

(untitled) - Zhang, L.-B.; Hao, X.-Q.; Zhang, S.-K.; Liu, Z.-J.; Zheng, X.-X.; Gong, J.-F.; Niu, J.-L.; Song, M.-P. (Angew. Chem., Int. Ed., 2015)

(untitled) - Chernyak, N.; Dudnik, A. S.; Huang, C.; Gevorgyan, V. (J. Am. Chem. Soc., 2010)

(untitled) - Huang, C.; Chernyak, N.; Dudnik, A. S.; Gevorgyan, V. (Adv. Synth. Catal., 2011)

(untitled) - Gulevich, A. V.; Melkonyan, F. S.; Sarkar, D.; Gevorgyan, V. (J. Am. Chem. Soc., 2012)

(untitled) - Sarkar, D.; Melkonyan, F. S.; Gulevich, A. V.; Gevorgyan, V. (Angew. Chem., Int. Ed., 2013)

(untitled) - Gao, T.; Sun, P. (J. Org. Chem., 2014)

(untitled) - Nakano, Y.; Lupton, D. W. (Chem. Commun., 2014)

(untitled) - Ju, L.; Yao, J.; Wu, Z.; Liu, Z.; Zhang, Y. (J. Org. Chem., 2013)

(untitled) - Cheng, T.; Yin, W.; Zhang, Y.; Zhang, Y.; Huang, Y. (Org. Biomol. Chem., 2014)

(untitled) - Jiang, H.; Chen, H.; Wang, A.; Liu, X. (Chem. Commun., 2010)

(untitled) - Zhang, S.; Luo, F.; Wang, W.; Jia, X.; Hu, M.; Cheng, J. (Tetrahedron Lett., 2010)

(untitled) - Wang, D.; Zavalij, P. Y.; Vedernikov, A. N. (Organometallics, 2013)

(untitled) - Shan, G.; Yang, X.; Zong, Y.; Rao, Y. (Angew. Chem., Int. Ed., 2013)

(untitled) - Zhou, L.; Lu, W. (Org. Lett., 2014)

(untitled) - Rit, R. K.; Yadav, M. R.; Sahoo, A. K. (Org. Lett., 2012)

(untitled) - Zong, Y.; Rao, Y. (Org. Lett., 2014)

(untitled) - Wu, X.; Zhao, Y.; Ge, H. (Chem. – Asian J., 2014)

(untitled) - Desai, L. V.; Hull, K. L.; Sanford, M. S. (J. Am. Chem. Soc., 2004)

(untitled) - Stowers, K. J.; Kubota, A.; Sanford, M. S. (Chem. Sci., 2012)

(untitled) - Giri, R.; Liang, J.; Lei, J.-G.; Li, J.-J.; Wang, D.-H.; Chen, X.; Naggar, I. C.; Guo, C.; Foxman, B. M.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2005)

(untitled) - Wang, Z.; Kuninobu, Y.; Kanai, M. (Org. Lett., 2014)

(untitled) - Owston, N. A.; Parker, A. J.; Williams, J. M. J. (Chem. Commun., 2008)

(untitled) - Owston, N. A.; Nixon, T. D.; Parker, A. J.; Whittlesey, M. K.; Williams, J. M. J. (Synthesis, 2009)

(untitled) - Yamamoto, N.; Obora, Y.; Ishii, Y. (J. Org. Chem., 2011)

(untitled) - Tschaen, B. A.; Schmink, J. R.; Molander, G. A. (Org. Lett., 2013)

(untitled) - Heropoulos, G. A.; Villalonga-Barber, C. (Tetrahedron Lett., 2011)

(untitled) - Liu, C.; Tang, S.; Zheng, L.; Liu, D.; Zhang, H.; Lei, A. (Angew. Chem., Int. Ed., 2012)

(untitled) - Liu, C.; Wang, J.; Meng, L.; Deng, Y.; Li, Y.; Lei, A. (Angew. Chem., Int. Ed., 2011)

(untitled) - Gowrisankar, S.; Neumann, H.; Beller, M. (Angew. Chem., Int. Ed., 2011)

(untitled) - Nielsen, I. S.; Taarning, E.; Egeblad, K.; Madsen, R.; Christensen, C. H. (Catal. Lett., 2007)

(untitled) - Marsden, C.; Taarning, E.; Hansen, D.; Johansen, L.; Klitgaard, S. K.; Egeblad, K.; Christensen, C. H. (Green Chem., 2008)

(untitled) - Fristrup, P.; Johansen, L. B.; Christensen, C. H. (Chem. Commun., 2008)

(untitled) - Su, F.-Z.; Ni, J.; Sun, H.; Cao, Y.; He, H.-Y.; Fa, K.-N. (Chem. – Eur. J., 2008)

(untitled) - Yasukawa, T.; Miyamura, H.; Kobayashi, S. (Chem. – Asian J., 2011)

(untitled) - Suzuki, K.; Yamaguchi, T.; Matsushita, K.; Iitsuka, C.; Miura, J.; Akaogi, T.; Ishida, H. (ACS Catal., 2013)

(untitled) - Noonan, C.; Baragwanath, L.; Connon, S. J. (Tetrahedron Lett., 2008)

(untitled) - Maki, B. E.; Scheidt, K. A. (Org. Lett., 2008)

(untitled) - Maki, B. E.; Chan, A.; Phillips, E. M.; Scheidt, K. A. (Tetrahedron, 2009)

(untitled) - Reddy, R. S.; Rosa, J. N.; Veiros, L. F.; Caddick, S.; Gois, P. M. P. (Org. Biomol. Chem., 2011)

(untitled) - Finney, E. E.; Ogawa, K. A.; Boydston, A. J. (J. Am. Chem. Soc., 2012)

(untitled) - Kiran, I. N. C.; Lalwani, K.; Sudalai, A. (RSC Adv., 2013)

(untitled) - Zhao, J.; Mück-Lichtenfeld, C.; Studer, A. (Adv. Synth. Catal., 2013)

(untitled) - Chiarotto, I.; Feroci, M.; Sotgiu, G.; Inesi, A. (Tetrahedron, 2013)

(untitled) - Ji, M.; Wang, X.; Lim, Y. N.; Kang, Y.-W.; Jang, H.-Y. (Eur. J. Org. Chem., 2013)

(untitled) - Maki, B. E.; Chan, A.; Phillips, E. M.; Scheidt, K. A. (Org. Lett., 2007)

(untitled) - Delany, E. G.; Fagan, C.-L.; Gundala, S.; Zeitler, K.; Connon, S. J. (Chem. Commun., 2013)

(untitled) - De Sarkar, S.; Grimme, S.; Studer, A. (J. Am. Chem. Soc., 2010)

(untitled) - Samanta, R. C.; De Sarkar, S.; Fröhlich, R.; Grimme, S.; Studer, A. (Chem. Sci., 2013)

(untitled) - Schmidt, A.; Habeck, T.; Snovydovych, B.; Eisfeld, W. (Org. Lett., 2007)

(untitled) - Cheng, S.; Chen, J.; Gao, W.; Jin, H.; Ding, J.; Wu, H. (J. Chem. Res., 2010)

(untitled) - Zhang, M.; Zhang, S.; Zhang, G.; Chen, F.; Cheng, J. (Tetrahedron Lett., 2011)

(untitled) - Valizadeh, H.; Ahmadi, M. (C. R. Chim., 2012)

(untitled) - Kuwano, S.; Harada, S.; Oriez, R.; Yamada, K. (Chem. Commun., 2012)

(untitled) - Delany, E. G.; Fagan, C.-L.; Gundala, S.; Mari, A.; Broja, T.; Zeitler, K.; Connon, S. J. (Chem. Commun., 2013)

(untitled) - Luo, F.; Pan, C.; Cheng, J.; Chen, F. (Tetrahedron, 2011)

(untitled) - Zhang, D.; Pan, C. (Catal. Commun., 2012)

(untitled) - Iwahana, S.; Iida, H.; Yashima, E. (Chem. – Eur. J., 2011)

(untitled) - De Sarkar, S.; Biswas, A.; Song, C. H.; Studer, A. (Synthesis, 2011)

(untitled) - Mori, N.; Togo, H. (Tetrahedron, 2005)

(untitled) - Yamada, S.; Morizono, D.; Yamamoto, K. (Tetrahedron Lett., 1992)

(untitled) - Reddy, K. R.; Venkateshwar, M.; Maheswari, C. U.; Prashanthi, S. (Synth. Commun., 2009)

(untitled) - Karade, N. N.; Budhewar, V. H.; Katkar, A. N.; Tiwari, G. B. (ARKIVOC, 2006)

(untitled) - Kiran, Y. B.; Ikeda, R.; Sakai, N.; Konakahara, T. (Synthesis, 2010)

(untitled) - Karade, N. N.; Shirodkar, S. G.; Dhoot, B. M.; Waghmare, P. B. (J. Chem. Res., 2005)

(untitled) - Shaikh, T. M. A.; Emmanuvel, L.; Sudalai, A. (Synth. Commun., 2007)

(untitled) - Leduc, A. B.; Jamison, T. F. (Org. Process Res. Dev., 2012)

(untitled) - Stevens, R. V.; Chapman, K. T.; Stubbs, C. A.; Tam, W. W.; Albizati, K. F. (Tetrahedron Lett., 1982)

(untitled) - Sayama, S. (Synlett, 2004)

(untitled) - Agrawal, M. K.; Adimurthy, S.; Ghosh, P. K. (Synth. Commun., 2012)

(untitled) - McDonald, C.; Holcomb, H.; Kennedy, K.; Kirkpatrick, E.; Leathers, T.; Vanemon, P. (J. Org. Chem., 1989)

(untitled) - Ghorbani-Vaghei, R.; Shahbazee, E.; Veisi, H. (Mendeleev Commun., 2005)

(untitled) - Liu, L.; Yun, L.; Wang, Z.; Fu, X.; Yan, C. (Tetrahedron Lett., 2013)

(untitled) - Feng, J.; Liang, S.; Chen, S.-Y.; Zhang, J.; Fu, S.-S.; Yu, X.-Q. (Adv. Synth. Catal., 2012)

(untitled) - Huang, J.; Li, L.-T.; Li, H.-Y.; Husan, E.; Wang, P.; Wang, B. (Chem. Commun., 2012)

(untitled) - Wei, W.; Zhang, C.; Xu, Y.; Wan, X. (Chem. Commun., 2011)

(untitled) - Zhu, F.; Wang, Z.-X. (Tetrahedron, 2014)

(untitled) - Tan, B.; Toda, N.; Barbas, C. F., III (Angew. Chem., Int. Ed., 2012)

(untitled) - Wang, G.; Yu, Q.-Y.; Wang, J.; Wang, S.; Chen, S.-Y.; Yu, X.-Q. (RSC Adv., 2013)

(untitled) - Wang, N.; Liu, R.; Xu, Q.; Liang, X. (Chem. Lett., 2006)

(untitled) - Schulze, A.; Giannis, A. (Adv. Synth. Catal., 2004)

(untitled) - Yao, H.; Tang, Y.; Yamamoto, K. (Tetrahedron Lett., 2012)

(untitled) - Toledo, H.; Pisarevsky, E.; Abramovich, A.; Szpilman, A. M. (Chem. Commun., 2013)

(untitled) - Rout, S. K.; Guin, S.; Ghara, K. K.; Banerjee, A.; Patel, B. K. (Org. Lett., 2012)

(untitled) - Raju, K. B.; Kumar, B. N.; Nagaiah, K. (RSC Adv., 2014)

(untitled) - Sharma, S.; Park, J.; Kim, M.; Kwak, J. H.; Jung, Y. H.; Kim, I. S. (Tetrahedron, 2013)

(untitled) - Yoo, W.-J.; Li, C.-J. (J. Org. Chem., 2006)

(untitled) - Kumar, G. S.; Maheswari, C. U.; Kumar, R. A.; Kantam, M. L.; Reddy, K. R. (Angew. Chem., Int. Ed., 2011)

(untitled) - Barve, B. D.; Wu, Y.-C.; El-Shazly, M.; Chuang, D.-W.; Chung, Y.-M.; Tsai, Y.-H.; Wu, S.-F.; Korinek, M.; Du, Y.-C.; Hsieh, C.-T.; Wang, J.-J.; Chang, F.-R. (Eur. J. Org. Chem., 2012)

(untitled) - Barve, B. D.; Wu, Y.-C.; El-Shazly, M.; Chuang, D.-W.; Cheng, Y.-B.; Wang, J.-J.; Chang, F.-R. (J. Org. Chem., 2014)

(untitled) - Saberi, D.; Heydari, A. (Tetrahedron Lett., 2013)

(untitled) - Phan, N. T. S.; Nguyen, T. T.; Vu, P. H. L. (ChemCatChem, 2013)

(untitled) - Gopinath, R.; Patel, B. K. (Org. Lett., 2000)

(untitled) - Gopinath, R.; Barkakaty, B.; Talukdar, B.; Patel, B. K. (J. Org. Chem., 2003)

(untitled) - Talukdar, D.; Sharma, K.; Bharadwaj, S. K.; Thakur, A. J. (Synlett, 2013)

(untitled) - Yoo, W.-J.; Li, C.-J. (Tetrahedron Lett., 2007)

(untitled) - Wu, X.-F.; Darcel, C. (Eur. J. Org. Chem., 2009)

(untitled) - Rafiee, E.; Eavani, S. (J. Mol. Catal. A: Chem., 2013)

(untitled) - Sharma, R. K.; Gulati, S. (J. Mol. Catal. A: Chem., 2012)

(untitled) - Esfandiari, H.; Jameh-bozorghi, S.; Esmaielzadeh, S.; Shafiee, M. R. M.; Ghashang, M. (Res. Chem. Intermed., 2013)

(untitled) - Wu, X.-F. (Tetrahedron Lett., 2012)

(untitled) - Zhao, J.; Fang, H.; Han, J.; Pan, Y. (Org. Lett., 2014)

(untitled) - O'Connor, B.; Just, G. (Tetrahedron Lett., 1987)

(untitled) - Sinha, A. K.; Sharma, A.; Swaroop, A.; Kumar, V. (Tetrahedron, 2007)

(untitled) - Sakuragi, H.; Tokumaru, K. (Chem. Lett., 1974)

(untitled) - Sundararaman, P.; Walker, E. C.; Djerassi, C. (Tetrahedron Lett., 1978)

(untitled) - Mineno, T.; Sakai, M.; Ubukata, A.; Nakahara, K.; Yoshimitsu, H.; Kansui, H. (Chem. Pharm. Bull., 2013)

(untitled) - Mineno, T.; Yoshino, S.; Ubukata, A. (Green Sustainable Chem., 2014)

(untitled) - Travis, B. R.; Sivakumar, M.; Hollist, G. O.; Borhan, B. (Org. Lett., 2003)

(untitled) - Nishihara, A.; Kubota, I. (J. Org. Chem., 1968)

(untitled) - Feng, J.-B.; Gong, J.-L.; Li, Q.; Wu, X.-F. (Tetrahedron Lett., 2014)

(untitled) - Tank, R.; Pathak, U.; Vimal, M.; Bhattacharyya, S.; Pandey, L. K. (Green Chem., 2011)

(untitled) - Kelly, C. B.; Mercadante, M. A.; Wiles, R. J.; Leadbeater, N. E. (Org. Lett., 2013)

(untitled) - Zhang, C.; Jiao, N. (Org. Chem. Front., 2014)

(untitled) - Srimani, D.; Balaraman, E.; Gnanaprakasam, B.; Ben-David, Y.; Milstein, D. (Adv. Synth. Catal., 2012)

(untitled) - Tanaka, A.; Moriyama, K.; Togo, H. (Synlett, 2011)

(untitled) - Hu, J.; Zhu, M.; Xu, Y.; Yan, J. (Synthesis, 2012)

(untitled) - Yu, J.; Tian, J.; Zhang, C. (Adv. Synth. Catal., 2010)

(untitled) - Yu, J.; Cui, J.; Hou, X.-S.; Liu, S.-S.; Gao, W.-C.; Jiang, S.; Tian, J.; Zhang, C. (Tetrahedron: Asymmetry, 2011)

(untitled) - Moriarty, R. M.; Vaid, R. K.; Ravikumar, V. T.; Vaid, B. K.; Hopkins, T. E. (Tetrahedron, 1988)

(untitled) - Price, D. A.; Gayton, S.; Stupple, P. A. (Synlett, 2002)

(untitled) - Liu, W.-B.; Chen, C.; Zhang, Q.; Zhu, Z.-B. (Bull. Korean Chem. Soc., 2012)

(untitled) - Yamamoto, Y.; Kawano, Y.; Toy, P. H.; Togo, H. (Tetrahedron, 2007)

(untitled) - Suzuki, Y.; Togo, H. (Synthesis, 2010)

(untitled) - Sheng, J.; Li, X.; Tang, M.; Gao, B.; Huang, G. (Synthesis, 2007)

(untitled) - Tanaka, A.; Togo, H. (Synlett, 2009)

(untitled) - Uyanik, M.; Suzuki, D.; Yasui, T.; Ishihara, K. (Angew. Chem., Int. Ed., 2011)

(untitled) - Li, X.; Zhou, C.; Xu, X. (ARKIVOC, 2012)

(untitled) - Guo, S.; Yu, J.-T.; Dai, Q.; Yang, H.; Cheng, J. (Chem. Commun., 2014)

(untitled) - Terent’ev, A. O.; Krylov, I. B.; Timofeev, V. P.; Starikova, Z. A.; Merkulova, V. M.; Ilovaisky, A. I.; Nikishin, G. I. (Adv. Synth. Catal., 2013)

(untitled) - Krylov, I. B.; Terent’ev, A. O.; Timofeev, V. P.; Shelimov, B. N.; Novikov, R. A.; Merkulova, V. M.; Nikishin, G. I. (Adv. Synth. Catal., 2014)

(untitled) - Terent'ev, A. O.; Borisov, D. A.; Yaremenko, I. A.; Chernyshev, V. V.; Nikishin, G. I. (J. Org. Chem., 2010)

(untitled) - Terent'ev, A. O.; Borisov, D. A.; Semenov, V. V.; Chernyshev, V. V.; Dembitsky, V. M.; Nikishin, G. I. (Synthesis, 2011)

(untitled) - Kharasch, M. S.; Fono, A. (J. Org. Chem., 1959)

(untitled) - Baidya, M.; Griffin, K. A.; Yamamoto, H. (J. Am. Chem. Soc., 2012)

(untitled) - Frazier, C. P.; Sandoval, D.; Palmer, L. I.; de Alaniz, J. R. (Chem. Sci., 2013)

(untitled) - Tanyeli, C.; Sezen, B. (Tetrahedron Lett., 2000)

(untitled) - Tanyeli, C.; Sezen, B.; İyigün, Ç.; Elmalı, O. (Tetrahedron Lett., 2001)

(untitled) - Tanyeli, C.; Özdemirhan, D.; Sezen, B. (Tetrahedron, 2002)

(untitled) - Tanyeli, C.; Tosun, A.; Turkut, E.; Sezen, B. (Tetrahedron, 2003)

(untitled) - Tanyeli, C.; Iyigün, Ç. (Tetrahedron, 2003)

(untitled) - Demir, A. S.; Reis, Ö.; Igdir, A. C. (Tetrahedron, 2004)

(untitled) - Demir, A. S.; Caliskan, Z.; Aydin, A. E.; Bicer, I. (Tetrahedron: Asymmetry, 2006)

(untitled) - Demir, A. S.; Findik, H. (Tetrahedron, 2008)

(untitled) - Marín-Barrios, R.; García-Cabeza, A. L.; Moreno-Dorado, F. J.; Guerra, F. M.; Massanet, G. M. (J. Org. Chem., 2014)

(untitled) - Kitching, W.; Rappoport, Z.; Winstein, S.; Young, W. G. (J. Am. Chem. Soc., 1966)

(untitled) - Engelin, C.; Jensen, T.; Rodriguez-Rodriguez, S.; Fristrup, P. (ACS Catal., 2013)

(untitled) - Grennberg, H.; Bäckvall, J.-E. (Chem. – Eur. J., 1998)

(untitled) - Diao, T.; Stahl, S. S. (Polyhedron, 2014)

(untitled) - Chen, M. S.; Prabagaran, N.; Labenz, N. A.; White, M. C. (J. Am. Chem. Soc., 2005)

(untitled) - Chen, M. S.; White, M. C. (J. Am. Chem. Soc., 2004)

(untitled) - Covell, D. J.; White, M. C. (Angew. Chem., Int. Ed., 2008)

(untitled) - Campbell, A. N.; White, P. B.; Guzei, I. A.; Stahl, S. S. (J. Am. Chem. Soc., 2010)

(untitled) - Mitsudome, T.; Umetani, T.; Nosaka, N.; Mori, K.; Mizugaki, T.; Ebitani, K.; Kaneda, K. (Angew. Chem., Int. Ed., 2006)

(untitled) - Vermeulen, N. A.; Delcamp, J. H.; White, M. C. (J. Am. Chem. Soc., 2010)

(untitled) - Thiery, E.; Aouf, C.; Belloy, J.; Harakat, D.; Le Bras, J.; Muzart, J. (J. Org. Chem., 2010)

(untitled) - Check, C. T.; Henderson, W. H.; Wray, B. C.; Vanden Eynden, M. J.; Stambuli, J. P. (J. Am. Chem. Soc., 2011)

(untitled) - Macsári, I.; Szabó, K. J. (Tetrahedron Lett., 1998)

(untitled) - García-Cabeza, A. L.; Marín-Barrios, R.; Moreno-Dorado, F. J.; Ortega, M. J.; Massanet, G. M.; Guerra, F. M. (Org. Lett., 2014)

(untitled) - Takemura, N.; Kuninobu, Y.; Kanai, M. (Org. Biomol. Chem., 2014)

(untitled) - Rout, S. K.; Guin, S.; Banerjee, A.; Khatun, N.; Gogoi, A.; Patel, B. K. (Org. Lett., 2013)

(untitled) - Rout, S. K.; Guin, S.; Ali, W.; Gogoi, A.; Patel, B. K. (Org. Lett., 2014)

(untitled) - Boldron, C.; Gamez, P.; Tooke, D. M.; Spek, A. L.; Reedijk, J. (Angew. Chem., Int. Ed., 2005)

(untitled) - Boldron, C.; Özalp-Yaman, Ş.; Gamez, P.; Tooke, D. M.; Spek, A. L.; Reedijk, J. (Dalton Trans., 2005)

(untitled) - Liu, H.; Shi, G.; Pan, S.; Jiang, Y.; Zhang, Y. (Org. Lett., 2013)

(untitled) - Benhmid, A.; Narayana, K. V.; Martin, A.; Lücke, B. (Chem. Commun., 2004)

(untitled) - Kalevaru, V. N.; Benhmid, A.; Radnik, J.; Pohl, M.-M.; Lücke, B.; Martin, A. (Catal. Today, 2009)

(untitled) - Gatla, S.; Madaan, N.; Radnik, J.; Kalevaru, V. N.; Pohl, M.-M.; Lücke, B.; Martin, A.; Brückner, A. (Appl. Catal., A, 2011)

(untitled) - Madaan, N.; Gatla, S.; Kalevaru, V. N.; Radnik, J.; Pohl, M.-M.; Lücke, B.; Brückner, A.; Martin, A. (ChemCatChem, 2013)

(untitled) - Shi, E.; Shao, Y.; Chen, S.; Hu, H.; Liu, Z.; Zhang, J.; Wan, X. (Org. Lett., 2012)

(untitled) - Majji, G.; Guin, S.; Gogoi, A.; Rout, S. K.; Patel, B. K. (Chem. Commun., 2013)

(untitled) - Xu, J.; Zhang, P.; Li, X.; Gao, Y.; Wu, J.; Tang, G.; Zhao, Y. (Adv. Synth. Catal., 2014)

(untitled) - Zaimoku, H.; Hatta, T.; Taniguchi, T.; Ishibashi, H. (Org. Lett., 2012)

(untitled) - Kumar, V.; Sharma, A.; Sharma, M.; Sharma, U. K.; Sinha, A. K. (Tetrahedron, 2007)

(untitled) - Yi, H.; Liu, Q.; Liu, J.; Zeng, Z.; Yang, Y.; Lei, A. (ChemSusChem, 2012)

(untitled) - Aubry, S.; Pellet-Rostaing, S.; Lemaire, M. (Eur. J. Org. Chem., 2007)

(untitled) - Estévez, J. C.; Villaverde, M. C.; Estévez, R. J.; Seijas, J. A.; Castedo, L. (Synth. Commun., 1990)

(untitled) - Guy, A.; Lemor, A.; Imbert, D.; Lemair, M. (Tetrahedron Lett., 1989)

(untitled) - Li, Y.; Bao, W. (Adv. Synth. Catal., 2009)

(untitled) - Mo, H.; Bao, W. (Tetrahedron, 2011)

(untitled) - Wang, T.; Zhou, W.; Yin, H.; Ma, J.-A.; Jiao, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Jin, J.; Li, Y.; Wang, Z.-j.; Qian, W.-x.; Bao, W.-l. (Eur. J. Org. Chem., 2010)

(untitled) - He, H.-F.; Wang, K.; Xing, B.; Sheng, G.; Ma, T.; Bao, W. (Synlett, 2013)

(untitled) - Bouquet, M.; Guy, A.; Lemaire, M.; Guetté, J. P. (Synth. Commun., 1985)

(untitled) - Lee, J. M.; Park, E. J.; Cho, S. H.; Chang, S. (J. Am. Chem. Soc., 2008)

(untitled) - Terent’ev, A. O.; Krylov, I. B.; Sharipov, M. Y.; Kazanskaya, Z. M.; Nikishin, G. I. (Tetrahedron, 2012)

(untitled) - Koshino, N.; Saha, B.; Espenson, J. H. (J. Org. Chem., 2003)

(untitled) - Terent’ev, A. O.; Krylov, I. B.; Lipatnikov, A. D. (Russ. J. Gen. Chem., 2014)
Zhurnal Obschei Khimii 2014, 84, 1786-1789.

(untitled) - Coseri, S. (Eur. J. Org. Chem., 2007)

(untitled) - Coseri, S. (J. Phys. Org. Chem., 2009)

(untitled) - Minisci, F.; Recupero, F.; Gambarotti, C.; Punta, C.; Paganelli, R. (Tetrahedron Lett., 2003)

(untitled) - Khan, K. M.; Maharvi, G. M.; Hayat, S.; Zia-Ullah; Choudhary, M. I.; Atta-ur-Rahman (Tetrahedron, 2003)

(untitled) - Iwata, S.; Hata, T.; Urabe, H. (Adv. Synth. Catal., 2012)

(untitled) - Macedo, A. G.; Fernandes, S. E. M.; Valente, A. A.; Ferreira, R. A. S.; Carlos, L. D.; Rocha, J. (Molecules, 2010)

(untitled) - Akhlaghinia, B.; Ebrahimabadi, H.; Goharshadi, E. K.; Samiee, S.; Rezazadeh, S. (J. Mol. Catal. A: Chem., 2012)

(untitled) - Shaikh, T. M.; Sudalai, A. (Tetrahedron Lett., 2005)

(untitled) - Khenkin, A. M.; Neumann, R. (J. Am. Chem. Soc., 2004)

(untitled) - Occhipinti, G.; Liguori, L.; Tsoukala, A.; Bjørsvik, H.-R. (Org. Process Res. Dev., 2010)

(untitled) - Cho, S.-D.; Kim, H.-J.; Ahn, C.; Falck, J. R.; Shin, D.-S. (Tetrahedron Lett., 1999)

(untitled) - Iwaoka, M.; Tomoda, S. (J. Chem. Soc., Chem. Commun., 1992)

(untitled) - Tiecco, M.; Testaferri, L.; Tingoli, M.; Bagnoli, L.; Santi, C. (J. Chem. Soc., Chem. Commun., 1993)

(untitled) - Shibuya, K. (Synth. Commun., 1994)

(untitled) - Chen, L.; Shi, E.; Liu, Z.; Chen, S.; Wei, W.; Li, H.; Xu, K.; Wan, X. (Chem. – Eur. J., 2011)

(untitled) - Zhang, S.; Guo, L.-N.; Wang, H.; Duan, X.-H. (Org. Biomol. Chem., 2013)

(untitled) - Yu, H.; Shen, J. (Org. Lett., 2014)

(untitled) - Zhao, J.; Fang, H.; Zhou, W.; Han, J.; Pan, Y. (J. Org. Chem., 2014)

(untitled) - Barve, B. D.; Wu, Y.-C.; El-Shazly, M.; Korinek, M.; Cheng, Y.-B.; Wang, J.-J.; Chang, F.-R. (Org. Lett., 2014)

(untitled) - Park, J.; Han, S. H.; Sharma, S.; Han, S.; Shin, Y.; Mishra, N. K.; Kwak, J. H.; Lee, C. H.; Lee, J.; Kim, I. S. (J. Org. Chem., 2014)

(untitled) - Phan, N. T. S.; Vu, P. H. L.; Nguyen, T. T. (J. Catal., 2013)

(untitled) - Murahash, S.-I.; Saito, T.; Naota, T.; Kumobayashi, H.; Akutagawa, S. (Tetrahedron Lett., 1991)

(untitled) - Murahashi, S.; Naota, T.; Kuwabara, T.; Saito, T.; Kumobayashi, H.; Akutagawa, S. (J. Am. Chem. Soc., 1990)

(untitled) - Shu, X.-Z.; Xia, X.-F.; Yang, Y.-F.; Ji, K.-G.; Liu, X.-Y.; Liang, Y.-M. (J. Org. Chem., 2009)

(untitled) - Weinberg, N. L.; Brown, E. A. (J. Org. Chem., 1966)

(untitled) - Liang, D.; Wang, M.; Dong, Y.; Guo, Y.; Liu, Q. (RSC Adv., 2014)

(untitled) - Liu, X.; Cheng, R.; Zhao, F.; Zhang-Negrerie, D.; Du, Y.; Zhao, K. (Org. Lett., 2012)

(untitled) - Liu, H.; Wang, X.; Gu, Y. (Org. Biomol. Chem., 2011)

(untitled) - Liu, H.; Xie, Y.; Gu, Y. (Tetrahedron Lett., 2011)

(untitled) - Jiang, Q.; Wang, J.-Y.; Guo, C. (J. Org. Chem., 2014)

(untitled) - Pelter, A.; Elgendy, S. M. A. (J. Chem. Soc., Perkin Trans. 1, 1993)

(untitled) - Fleck, A. E.; Hobart, J. A.; Morrow, G. W. (Synth. Commun., 1992)

(untitled) - Mitchell, A. S.; Russell, R. A. (Tetrahedron Lett., 1993)

(untitled) - Omura, K. (Synthesis, 2010)

(untitled) - Chen, X.; Zhu, C.; Cui, X.; Wu, Y. (Chem. Commun., 2013)

(untitled) - Takemura, N.; Kuninobu, Y.; Kanai, M. (Org. Lett., 2013)

(untitled) - Halper, S. R.; Stork, J. R.; Cohen, S. M. (Dalton Trans., 2007)

(untitled) - Takuwa, A.; Soga, O.; Iwamoto, H.; Maruyama, K. (Bull. Chem. Soc. Jpn., 1986)

(untitled) - Kidwai, M.; Kumar, P.; Kohli, S. (J. Chem. Res., Synop., 1997)

(untitled) - Bansal, V.; Sharma, J.; Khanna, R. N. (J. Chem. Res., Synop., 1998)

(untitled) - Komiya, N.; Noji, S.; Murahashi, S.-I. (Chem. Commun., 2001)

(untitled) - Nomura, K.; Uemura, S. (J. Chem. Soc., Chem. Commun., 1994)

(untitled) - Deno, N. C.; Messer, L. A. (J. Chem. Soc., Chem. Commun., 1976)

(untitled) - Moody, C. J.; O’Connell, J. L. (Chem. Commun., 2000)

(untitled) - Tran, B. L.; Driess, M.; Hartwig, J. F. (J. Am. Chem. Soc., 2014)

(untitled) - Gary, J. B.; Cook, A. K.; Sanford, M. S. (ACS Catal., 2013)

(untitled) - Tajima, T.; Fuchigami, T. (Chem. – Eur. J., 2005)